Edukasi Bridging Exercise untuk Meningkatkan Kemampuan Kontrol Mikturisi pada Kelompok Lansia di Puskesmas Rappang Kabupaten Sidrap - Abdul Majid; Wa Ode Nur Isnah; Ita Rini; A Muflihah Darwis; Yeri Mustari (Universitas Baiturrahim, 2026)
Urinary control disorders in the elderly are significant health problems that greatly affect quality of life, including decreased self-confidence and an increased risk of social isolation. Data from the Rappang Public Health Center, Sidrap Regency, in 2024 showed that approximately 35% of older adults experienced this condition. One effective intervention to address this problem is Bridging Exercise, a simple exercise aimed at strengthening the pelvic floor muscles. This community service activity aimed to improve the knowledge and skills of older adults in performing Bridging Exercise independently through education and demonstration. The activity was conducted at the Rappang Public Health Center, Sidenreng Rappang Regency, on Thursday, June 12, 2025, involving 51 older adults aged ≥65 years. The educational media used included PowerPoint presentations and leaflets, accompanied by direct demonstrations of Bridging Exercise movements. The pre-test and post-test results showed an increase in older adults knowledge from 2.0% to 76.5% after the intervention. These findings indicate that education combined with demonstration is effective in improving older adults’ understanding and skills and has the potential to be applied as a promotive and preventive intervention in older adult health services